BLOGGING ONLINE LEARNING NEWS AND RESEARCH - Schroeder, Ray (Online Learning, 2003)
Those in the field of ALN are confronted with the challenge of keeping up with the rapidly evolving processes, technologies, environments and current findings of the field. As director of technology-enhanced learning at the University of Illinois at Springfield (UIS), I am charged with seeking out the latest developments and sharing them with our online faculty members. In this case study, I describe the process of identifying current developments, filtering them to meet faculty interests and the use of web log (blog) technologies to disseminate the information to faculty members at UIS and elsewhere.